Induction of Protocorm-Like Bodies (PLBs) Phalaenopsis spp. Hybrids Mutation through Ultraviolet Irradiation (UV254) and Ethyl Methane Sulfonate (EMS) - Agatha Sullivania Kurniadi; Fenny Irawati; Sulistyo Emantoko Dwi Putra; Poppy Hartatie Hardjo (Politeknik Negeri Jember, 2023)
Phalaenopsis sp. is the most-produced orchid species in Indonesia. Compared to conventional breeding, mutation induction by using mutagens, such as Ultraviolet Light-C (λ = 254 nm) (UV254) and Ethyl Methane Sulfonate (EMS), could probably result in new superior orchid variants. This research aims to get some mutants with phenotypes that have visual differences in the Phalaenopsis spp. hybrids wild type. There were 4 durations of UV254 irradiation: 5’ on, 85’ off; 10’ on, 80’ off (1 day and 7 days for each treatment); 4 concentrations of EMS used in this research: 0.05%; 0.06%; 0.07%; 0.08% for 6 hours of immersion; selected UV254 irradiation (5’ on, 85’ off (7 days)) combined with these concentrations. UV254 irradiation treatment (5’ on, 85’ off (1 day and 7 days); 10’ on, 80’ off (7 days)) resulted in some mutants with leaf phenotypes that were visually different from the wild type; 0.05% EMS treatment resulted in PLBs mutant with a visually larger size than the wild type; 0.08% EMS treatment and combination treatments (for EMS 0.05% and 0.08% for each treatment) resulted in non-growing albino PLBs. Hence, mutation induction using UV254 and EMS in this research produced several most likely mutants having visual differences that may be more desirable than the wild type.